Comparative analysis of timely loss recognition during local and international accounting standards regimes: Case of listed manufacturing firms in Nigeria - Alade, Muyiwa Ezekiel (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The study investigates the pattern of timely loss recognition among listed manufacturing firms in Nigeria before and after the implementation of the International Financial Reporting Standard (IFRS). This effort was made by the craving of the accounting standards’ setters to continue ascertaining the quality of accounting standards issued under IFRS and its implication on accounting information issued during the reporting regime. The study relied on ex post facto research, and secondary data covering a 7-year period before and a 7-year period after IFRS implementation were drawn from the annual reports of 17 purposively selected manufacturing firms listed on the Nigerian Exchange Group (NGX), using certain selection criteria. Results based on a panel regression test reveal higher timely recognition of losses during the IFRS reporting period than the period before IFRS implementation. The result of the interactive terms and timey losses also reveals the existence of earnings smoothing in the pre-IFRS period, which seems to have been informed by less timely loss recognition. Thus, the study concludes that more losses are recognized by conservative corporate managers during the IFRS reporting period based on this context. The findings have implications for the potential investors, lenders of excess liquidity, and standard setters, among others.